Irradiation Induced Fluorescence Enhancement in PEGylated Cyanine-based NIR Nano- and Meso-scale GUMBOS - Lu, Chengfei (2012)
We report on the synthesis and characterization of a PEGylated IR786 GUMBOS (Group of Uniform Materials Based on Organic Salts). The synthesis of this material was accomplished using a three step protocol: (1) substitution of chloride on the cyclohexenyl ring in the heptamethine chain of IR786 by 6-aminohexanoic acid, (2) grafting of methoxy poly ethyleneglycol (MeOPEG) onto the 6-aminohexanoic acid via an esterification reaction, and (3) anion exchange between [PEG786][I] and lithium bis(trifluoromethylsulfonyl)imide (LiNTf(2)) or sodium bis(2-ethylhexyl)sulfosuccinate (AOT) in order to obtain PEG786 GUMBOS. Examination of spectroscopic data for this PEG786 GUMBOS indicates a large stokes shift (122 nm). It was observed that this PEG786 GUMBOS associates in aqueous solution to form nano-and meso-scale self-assemblies with sizes ranging from 100 to 220 nm. These nano- and meso-scale GUMBOS are also able to resist nonspecific binding to proteins. PEGylation of the original IR786 leads to reduced cytotoxicity. In addition, it was noted that anions, such as NTf(2) and AOT, play a significant role in improving the photostability of PEG786 GUMBOS. Irradiation-induced J aggregation in [PEG786][NTf(2)] and to some extent in [PEG786][AOT] produced enhanced photostability. This observation was supported by use of both steady state and time-resolved fluorescence measurements.